TEACHING ENGLISH AS A SECOND OR FOREIGN LANGUAGE, MULTILINGUAL SETTING AND TEACHING TECHNIQUES - Juraeva, Madinabonu Shermuhammad qizi (Educational Research in Universal Sciences, 2024)
All living creatures have some means of conveying information to others of their own group, communication being ultimately essential for their survival. Some use vocal noises, others physical movement or facial expression. Many employ a variety of methods. Birds use predominantly vocal signals, but also show their intentions by body movements; animals use vocal noises as well as facial expressions like the baring of teeth; insects use body movements, the most famous of which are the various ‘dances’ of the bees.